The Influence of Service Quality, Ease of Use, and Trust on User Satisfaction of BNI Mobile Banking - Putra Apriandika; Aldina Shiratina (Jurnal Manajemen Sinergi, 2024)
ABSTRACTObjective: This study aims to analyze the effects of service quality, ease of use, and trust on user satisfaction with mobile banking in Indonesia, specifically at Bank BNI.Methodology: This research employs a quantitative approach with the population consisting of users of BNI's mobile banking. A total of 160 respondents aged 18 to 55 years were selected as samples using the Hair formula and purposive sampling technique. Data was collected through a survey using a questionnaire distributed via Google Form. Data analysis was conducted using Structural Equation Modeling (SEM) with SmartPLS softwareFindings: The analysis results indicate that service quality has a positive and significant effect on user satisfaction, with an original sample value of 0.220 and a T-statistic of 2.166. Ease of use also shows a positive and significant effect with an original sample of 0.439 and a T-statistic of 5.268. Additionally, trust positively and significantly affects user satisfaction with an original sample of 0.214.Conclusion: These findings indicate that factors such as service quality, ease of use, and trust have a significant influence on user satisfaction with mobile banking at Bank BNI. This research provides important insights for the bank in efforts to enhance mobile banking services and user satisfaction.